Colaboração e compartilhamento da informação no ambiente organizacional - Alessandra Maria Alves (2011)
This study aimed identify factors that influence the exchange of information through the use of collaborative systems (or social networking tools) in the organizational environment. This in an attempt to also recognize what kinds of information exchanges (if shared or collaborative) prevail in this context. For this, we tried to structure the study based on an extensive literature review on the issues associated with research, including topics such as information behavior, factors that influence the exchange of information (including the motivation - including McClellands Acquired Needs Theory, organizational culture, power in organizations, trust, reciprocity, etc.), CSCW, groupware, collaborative systems, social networking tools, etc.. Among the topics discussed in the literature review are also the terms collaboration and sharing of information, which although they are often used as synonyms in the search have different meanings and quite significant in the context of information exchanges. The literature review addressed a set of concepts and expressions in order to support the exploratory research, which was applied in three Brazilian companies of different sizes and business. To participate in this study, companies should have certain requirements, among them, have implemented a collaborative system for over a year, in order to contribute to the validity of the research. To apply the research, we used quantitative and qualitative research techniques through the application of mixed research methods. To represent the quantitative research we used the online questionnaire distributed to employees who actually use the collaborative system adopted by the three participating companies. And to contribute to the qualitative data collection, was used of semi-structured interviews applied with the managers of the teams of users of the collaborative system, as well as those responsible for implementing the same in the organizations of the study. Analysis and interpretation of data were performed separately according to the alternative strategy of mixed methods - sequential exploratory project, which stipulates the priority for the method of quantitative research and data integration only in the interpretation phase, the analysis being performed on a stage pre-trial. The survey results reveal the existence of a strong association between the factors that influence the exchange of information and the reasons that encourage relationship behavior, performance and / or power and status, adopted the McClellands Acquired Needs Theory. And while the study is composed of companies of all sizes and differentiated businesses, we found similarities in the results, especially for the reason that encourages behavior that all of them was the reason for the relationship. Another important point in analyzing the data is to the strong influence of organizational culture, technology and the profile of the individual as well as the co-existence of two types of information sharing (sharing and collaboration) in the use of collaborative systems in all organizations.